The Fast Forward MBA in Project Management - Verzuh, Eric (Ascent Audio, 2021)
The Fast Forward MBA in Project Management is the comprehensive guide to real-world project management methods, tools, and techniques. Practical, easy-to-use, and deeply thorough, this book gives you answers you need now. You'll find the cutting-edge ideas and hard-won wisdom of one of the field's leading experts, delivered in short, lively segments that address common management issues. Brief descriptions of important concepts, tips on real-world applications, and compact case studies illustrate the most sought-after skills and the pitfalls you should watch out for. This new fifth edition features new case studies, new information on engaging stakeholders, change management, new guidance on using Agile techniques, and new content that integrates current events and trends in the project management sphere. Project management is a complex role, with seemingly conflicting demands that must be coordinated into a single, overarching, executable strategy-all within certain time, resource, and budget constraints. This book shows you how to get it all together and get it done, with expert guidance every step of the way. Disclaimer: This audiobook refers to figures, tables, and an Appendix included in the print and eBook editions of the book.